Bimetallic multifunctional nanostructures based on Cu–Ni alloy for environmental sensing and catalysis applications. (February 2021) - Renganathan, Vengudusamy; Balaji, Ramachandran; Chen, Shen-Ming; Chen, Tse-Wei; Ali, Mohammad Ajmal; Al-Hemaid, Fahad; El-Shikh, Mohammad Soliman
Abstract: An efficient electrochemical sensing and catalysis platform based on Cu–Ni alloy is developed. The Cu–Ni alloy (CN) are synthesized using ultrasonic aided thermal annealing process. The synthesized Cu–Ni nanostructures are thoroughly characterized for its crystallinity, morphology and topography. For the electrochemical sensing, the resorcinol is chosen as analyte and for catalyst assisted chemical degradation process, methylene blue is selected as an analyte. Upon electrochemical sensing investigation, Cu–Ni alloy based sensor exhibited superior sensitivity of 7.9472 μAμM −1 cm −2 and current responses are linear over the concentration range from 0.01 to 5.59 μM. The limit of detection (LOD) and limit of quantification (LOQ) of the sensor is estimated to be 5.24 nM and 0.0175 μM. The sensor is successfully tested for real time environmental samples. In the catalyst assisted chemical degradation of the methylene blue dye investigation, our catalyst Cu–Ni alloy accelerated the degradation of methylene blue in 9 min. Highlights: We fabricated a bifunctional nanocomposite based on Cu–Ni Alloy via ultrasonic assisted thermal annealing approach. As prepared, Cu–Ni alloy was successfully applied for the electrochemical detection of resorcinol (RC) and catalytic degradation of Methylene Blue (MB) for the first time. The Cu–Ni modified electrode exhibits wide linear range and low limit of detection of about 0.01–5.59 μM and 5.24 nM towards RC detection. The real sample analysis reveals the practical applicability of Cu–Ni modified electrode for sensing of RC in environmental water samples. Cu–Ni alloy accelerated the MB degradation in 9 min.